A Methodological Note on the Study of Queuing Networks - Ferreira, M. A. M.; Andrade, M. A. P. (EasyChair Preprint Nº 8361, 2025)
The objective of this note is to present a theorem about the approximation of any distribution by a mixture of Gama distributions, that allows to consider directly infinite states space in the study of queuing networks systems.